Minimally invasive treatment for glioblastoma through endoscopic surgery including tumor embolization when necessary: a technical note - Sakata, Tomohiro; Tanikawa, Motoki; Yamada, Hiroshi; Fujinami, Ryota; Nishikawa, Yusuke; Yamada, Shigeki; Mase, Mitsuhito (Frontiers in Neurology, 2023)
Background Although there have been some reports on endoscopic glioblastoma surgery, the indication has been limited to deep-seated lesions, and the difficulty of hemostasis has been a concern. In that light, we attempted to establish an endoscopic procedure for excision of glioblastoma which could be applied even to hypervascular or superficial lesions, in combination with pre-operative endovascular tumor embolization. Methods Medical records of six consecutive glioblastoma patients who received exclusive endoscopic removal between September and November 2020 were analyzed. Preoperative tumor embolization was performed in cases with marked tumor stain and proper feeder arteries having an abnormal shape, for instance, tortuous or dilated, without passing through branches to the normal brain. Endoscopic tumor removal through a key-hole craniotomy was performed by using an inside-out excision for a deep-seated lesion, with the addition of an outside-in extirpation for a shallow portion when needed. Results Endoscopic removal was successfully performed in all six cases. Before resection, endovascular tumor embolization was performed in four cases with no resulting complications, including ischemia or brain swelling. Gross total resection was achieved in three cases, and near total resection in the other three cases. Intraoperative blood loss exceeded 1,000 ml in only one case, whose tumor showed a prominent tumor stain but no proper feeder artery for embolization. In all patients, a smooth transition to adjuvant therapy was possible with no surgical site infection. Conclusion Endoscopic removal for glioblastoma was considered to be a promising procedure with minimal invasiveness and a favorable impact on prognosis.